Uncertainty in Economic Policy and Corporate Risk-taking: Product Market Competition, Financial Friction, and Financialization - Mohammad Omid Akhgar; Zanyar Sajjadi; nader Rasooli kordestani (بررسی‌های حسابداری و حسابرسی)
Objective In recent years, the volatility of macroeconomic variables and the opacity surrounding the general direction of government economic policies have fostered an environment of uncertainty for the country's economic activities. The occurrence of economic policy uncertainty makes it more difficult for companies to secure financial resources, and they may not be able to support high-risk and high-yield investment projects due to a lack of funds. Companies become more risk-averse due to the shock of economic policy uncertainty. This relationship is valid under the criteria of unstable risk and profit volatility, regardless of whether the macroeconomic conditions are favorable or not. The effect of economic policy uncertainty on corporate risk-taking is also affected by product market competition and financial friction. Accordingly, the main purpose of this study is to identify the relationship between economic policy uncertainty and corporate risk-taking with the moderating role of product market competition and financial friction and the mediating role of financialization among the listed companies at the Tehran Stock Exchange. Methods This research is practical in terms of its objective. It employs descriptive-correlational research methodology, utilizing regression and correlation techniques to explore the relationship between variables. Thus, in terms of reasoning, it falls within the realm of inductive research. In this way, in terms of reasoning, it is placed in the group of inductive research. Additionally, this study embodies a positive theory, as conclusions are drawn based on the examination and testing of existing data. To achieve the goal of the research, 142 companies were selected as available samples from 2010 to 2019, and a total of 1,420 companies were examined for analysis. The uncertainty of economic policy was calculated using the seasonal economic indicators available on the Central Bank of Iran website for the Iranian years 1378 to 1399 (1999 to 2020). Ordinary least squares regression, Sobel test, and Panel data were used to test the research hypotheses. Results According to the achieved results, there is a positive and significant relationship between economic policy uncertainty and corporate risk-taking. However, no evidence was found to indicate the moderating role of product market competition and financial friction on the relationship between economic policy uncertainty and corporate risk-taking. There is a negative and significant relationship between the uncertainty of economic policy and financialization, and as the uncertainty of economic policy increases, the level of financial assets in companies decreases. By entering financialization as a mediating variable in the main model, the mediating role is not confirmed. Conclusion As the findings showed, economic policy uncertainty leads to stronger risk-taking motivations i.e. when economic policy uncertainty is high, the motivation of the firm to invest is mainly opportunity expectations rather than risk aversion. The greater the uncertainty of economic policy, the more companies tend to accept risk to adapt to the market, achieve optimal performance, and use profitable opportunities. As economic policy uncertainty increases, the level of financial assets in companies decreases. In other words, companies are not separated from their main activities and are focused on investing and creating profitability in their main activities.